Essential Role of the E3 Ubiquitin Ligase NOPPERABO1 in Schizogenous Intercellular Space Formation in the Liverwort Marchantia polymorpha([W]) - Ishizaki, Kimitsune (American Society of Plant Biologists, 2013)
The vast majority of land plants develop gas-exchange tissues with intercellular spaces (ICSs) connected directly to the air. Although the developmental processes of ICS have been described in detail at the morphological and ultrastructural level in diverse land plants, little is known about the molecular mechanism responsible for ICS formation. The liverwort Marchantia polymorpha develops a multilayered tissue with a large ICS (air chamber), whose formation is initiated at selected positions of epidermal cells. We isolated a mutant of M. polymorpha showing impaired air-chamber formation, nopperabo1 (nop1), from T-DNA–tagged lines. In nop1 plants, no ICS was formed; consequently, a single-layered epidermis developed on the dorsal side of the thallus. The causal gene NOP1 encodes a Plant U-box (PUB) E3 ubiquitin ligase carrying tandem ARMADILLO (ARM) repeats in the C terminus. An in vitro ubiquitination assay indicated that the NOP1 protein possesses E3 ubiquitin ligase activity in a U-box–dependent manner. Confocal microscopy and biochemical analysis showed that NOP1 was localized to the plasma membrane. Our investigation demonstrated the essential role of the PUB-ARM–type ubiquitin ligase in ICS formation in M. polymorpha, which sheds light on the molecular mechanism of schizogenous ICS formation in land plants.